An image engineering approach to analysing mobile mapping data - Borck, Michael; West, Geoff; Tan, Tele (CEUR Workshop Proceedings (CEUR-WS.org) Online Proceedings for Scientific Workshops, 2014)
Vehicle-based mobile mapping systems capture co-registered imagery and 3D point cloud information over hundreds of kilometres of transport corridor. Methods for extracting information from these large datasets are labour intensive. These need to be easily configured by non-expert users to process images and develop new workflows. Image Engineering provides a framework to combine known image processing, image analysis an image understanding methods into powerful applications. Such a system was built using Orange an open source toolkit for machine learning onto which image processing, visualisation and data acquisition methods were added. The system presented here enable users who are not programmers to manage image data and to customise their analyses by combining common data analysis tools to fit their needs. Case studies are provided to demonstrate the utility of the system. Co-registered imagery and depth data of urban transport corridors provided by the Earthmine dataset and laser ranging systems are used.